2022
DOI: 10.1007/s11065-022-09536-5
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective Memory Training in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Prospective memory (PM), which enables one to remember to carry out delayed intentions, is crucial for everyday functioning. PM commonly deteriorates upon cognitive decline in older adults, but several studies have shown that PM in older adults can be improved by training. The current study aimed to summarise this evidence by conducting a qualitative systematic analysis and quantitative meta-analysis of the effects of PM training in older adults, for which systematic searches were conducted across seven databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
(238 reference statements)
0
2
0
Order By: Relevance
“…Greater coherence between areas could be interpreted in the context of hyperconnectivity ( Hillary and Grafman, 2017 ), suggesting that improved connectivity between brain regions may represent a mechanism of plasticity ( Bonanni et al, 2021 ). Since prospective memory serves as a predictive indicator of cognitive behavior in healthy older adults ( Tse et al, 2023 ), the correlation between scores of this type of memory and coherence between regions of different bands was calculated. The results showed an inverse relationship between prospective memory scores and increased coherence between anterior and anteroposterior areas of theta and alpha bands during the EC condition and in the beta band during EO .…”
Section: Discussionmentioning
confidence: 99%
“…Greater coherence between areas could be interpreted in the context of hyperconnectivity ( Hillary and Grafman, 2017 ), suggesting that improved connectivity between brain regions may represent a mechanism of plasticity ( Bonanni et al, 2021 ). Since prospective memory serves as a predictive indicator of cognitive behavior in healthy older adults ( Tse et al, 2023 ), the correlation between scores of this type of memory and coherence between regions of different bands was calculated. The results showed an inverse relationship between prospective memory scores and increased coherence between anterior and anteroposterior areas of theta and alpha bands during the EC condition and in the beta band during EO .…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic qualitative analysis, coupled with a quantitative meta-analysis on the impact of prospective memory (PM) training in older adults, it was indicated that there was a notable but modest immediate effectiveness of PM training in enhancing PM performance. However, no significant long-term effectiveness was discerned [ 100 ]. Similarly, reviews proposed that not only the specific training strategies employed for the assessment of prospective memory need to be further examined, but also certain parameters need to be considered, such as the participants’ digital literacy as well as their motor and sensory restrictions [ 101 , 102 ].…”
Section: Literature Review On Computerized Memory Assisting Technologiesmentioning
confidence: 99%